2008
DOI: 10.1093/carcin/bgn141
|View full text |Cite
|
Sign up to set email alerts
|

Genetic deficiency of decorin causes intestinal tumor formation through disruption of intestinal cell maturation

Abstract: Decorin is a member of the small leucine-rich proteoglycan gene family and plays an important role in suppressing cancer cell growth and metastasis. To elucidate the importance of decorin in intestinal carcinogenesis, a decorin-deficient (Dcn(-/-)) mouse model was employed. We found that targeted inactivation of decorin was sufficient to cause intestinal tumor formation with 30% of the Dcn(-/-) mice developing intestinal tumors with no other chemical or genetic initiation. Moreover, a high-risk diet amplified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
113
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(125 citation statements)
references
References 33 publications
7
113
0
Order By: Relevance
“…Compelling evidence has shown that DCN contributes to inhibition of tumor growth and metastasis (13,(15)(16)(17)(18)(19)34). Goldoni et al reported that DCN can display an anti-metastatic role in breast cancer (16).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Compelling evidence has shown that DCN contributes to inhibition of tumor growth and metastasis (13,(15)(16)(17)(18)(19)34). Goldoni et al reported that DCN can display an anti-metastatic role in breast cancer (16).…”
Section: Discussionmentioning
confidence: 99%
“…Goldoni et al reported that DCN can display an anti-metastatic role in breast cancer (16). Bi et al demonstrated that DCN may act as a tumor suppressor gene (15) and mediate inhibition of colorectal cancer growth and migration (13). Among soft tissue tumor patients with recurrent or metastatic lesions, lower levels of DCN were expressed in secondary lesions than those in primary lesions (17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with this hypothesis, a recent study utilizing decorin-null animals, which were backcrossed into a different genetic background, has shown that the lack of decorin favors spontaneous occurrence of intestinal tumors in Ïł30% of the cases, and this tumor burden and frequency were exacerbated by subjecting the mutant mice to a high risk diet (35).…”
mentioning
confidence: 90%